Hubungan antara Sabar dan Kesejahteraan Psikologis pada Volunteer di Kelas Play and Friendship Art Therapy Center - Bilqis Rizma Ahmadia; Elza Sabillah (Batanang : Jurnal Psikologi, 2025)
The growing phenomenon of volunteerism among students, especially in social activities related to children with special needs. These activities require a high level of patience and can affect the psychological well-being of volunteers. The purpose of this study was to determine the level of patience, psychological well-being, and the relationship between the two in volunteers in the Play and Friendship class. The method used was quantitative with a correlational approach. The research subjects consisted of 30 active volunteers selected using saturated sampling and purposive sampling techniques. The results showed that most volunteers had a moderate level of patience (73.3%) and moderate psychological well-being (50%). The correlation test produced a value of r = 0.637 with p < 0.001, which means that there is a positive and significant relationship between patience and psychological well-being. The higher the level of patience, the higher the level of psychological well-being of volunteers.